Evolution and magnetic characteristics of NiO-Ni(OH)(2) core-shell nanostructures - Mahajan, Mangesh B.; Joy, Pattayil Alias (Physical Chemistry Chemical Physics, 2013)
The evolution and magnetic behaviour of NiO-Ni(OH)(2) core-shell nanostructures with different thicknesses of the hydroxide shell have been studied. The nickel hydroxide shell is found to alter the magnetic characteristics of nickel oxide at low temperatures and explains the origin of the exchange bias effect due to the anti-ferromagnetic NiO core and a ferromagnetic nickel hydroxide shell.